2010
DOI: 10.1021/je100389d
|View full text |Cite
|
Sign up to set email alerts
|

Solubilities of Dichloromethane, Diethyl Ether, Ethyl Acetate, and Nitrobenzene in Three Polymers Using the Piezoelectric Quartz Sorption Method

Abstract: The solubilities of dichloromethane, diethyl ether, ethyl acetate, nitrobenzene in polyisobutylene (PIB), poly(nbutyl methacrylate) (PBMA), and poly(vinyl acetate) (PVAc) were measured by the piezoelectric quartz crystal microbalance method at four temperatures, (293.2, 313.2, 333.2, and 353.2) K. In this work, three quartz crystals were installed in an equilibrium cell, which enables multiple solubility measurements. The estimated experimental uncertainty was less than 1 % for solvent activity and 6.6 % mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Figure compares the results of the present study for dichloromethane + PBMA to those reported by Wibawa et al at the same temperature and polymer molecular weight conditions as for benzene and 2-butanone. Here, the temperature dependence suggested by the latter study is much larger than for the other two systems under comparison, and the activities reported by the two investigations are not in agreement.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…Figure compares the results of the present study for dichloromethane + PBMA to those reported by Wibawa et al at the same temperature and polymer molecular weight conditions as for benzene and 2-butanone. Here, the temperature dependence suggested by the latter study is much larger than for the other two systems under comparison, and the activities reported by the two investigations are not in agreement.…”
Section: Resultssupporting
confidence: 75%
“…The activities of benzene in poly­(butyl methacrylate) at 323.65 K were reported by Wohlfarth for solvent weight fractions of between approximately 0.3 and 0.5 and at 293.2 to 353.2 K by Wibabwa et al for solvent weight fractions up to about 0.3. Activities in poly­(butyl methacrylate) under conditions similar to those in ref have been reported for 2-butanone and dichloromethane …”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…While QCM-D gas uptake experiments involving chemical warfare agents and other volatile organic compounds are not novel, QCM-D use has seen limited application in probing fundamental interactions in gas-polymer systems. [5][6][7][8]…”
Section: Introduction mentioning
confidence: 99%